Estudo do comportamento de um pequeno aquífero aluvial na bacia experimental de Santana do Ipanema: semi-árido alagoano - Santos, Magaly Vieira Costa dos (2009)
The importance of studies in alluvial aquifer in the semi-arid is evidenced when it is taken in consideration that, a lot of times, these are constantly the base of the development of areas affected for the climatic phenomena, especially the droughts. In the Experimental Basin of Santana of Ipanema was installed an experimental apparatus, composed of a battery of fifteen piezometer, seeking to know the dynamics of the alluvial aquifer in the area. The place comes with typical characteristics of the semi-arid Brazilian, where the variability of the regime pluviometer, associated to the discharges evaporation rates, does with that the drought is the main factor limiting for the socioeconomic development of the area. Starting from the continuous monitoring of the components of the system, it was made a global characterization regarding the aquifer in study. Besides, analyses accomplished in field campaigns they allowed to do a simplified characterization of the parameters as well as the estimate of your potentialities. It was also developed a model based on statistical techniques with the objective of explaining the behavior of the aquifer during the observation period. The result of this was quite representative in what refers the observed monthly situation, being this committed, for the little period of observation of data. Finally, MODFLOW was used, to do calibration of the data in the permanent regime, it is verified that the flow lines were shown coherent with the other accomplished observations. As general result, is verified that basically the feeding of the aquifer is processed by recharge direct, originating from the precipitation, and that there is you evidence of the lateral contribution in the area in study, probably for the located dam beside the area in study. Another important verification is that inferior monthly precipitations to 100 mm aren’t capable to saturate the soil to favor the feeding of the aquifer. Such results, verified through statistical techniques and of mathematical models, beyond field verifications, appear as common strategies, but that can be capable to evaluate the behavior of alluvial aquifer sufficiently, in way to subsidize actions that allow to obtain more detailed knowledge on such systems.